Challenges and Perspectives of Development of Private Pension Funds in Serbia - Marija Đekić; Miloš Nikolić; Tamara Vesić (Economic Analysis, 2019)
Following the successful implementation of the Chilean reform, the World Bank proposed a solution from three pillars of the pension system: compulsory state, compulsory private and voluntary private pension insurance. Serbia, like many other developed and undeveloped countries, has only adopted the third pillar, in addition to the already existing state. The introduction of compulsory private insurance was also considered. However, there are no market conditions or financial possibilities for achieving this idea. Voluntary pension funds in Serbia were introduced by the 2005 laws. There are seven voluntary pension funds in Serbia, managed by four management companies. So far, the funds have achieved positive yields, although due to limited investment opportunities, these rates were very modest. In addition to limited investment opportunities, one of the problems is the accumulation of funds. The problem of population savings has many sides, and it is certain that some of the causes can be sought in bad experiences from the past. The paper analyses the limitations and possibilities for further development of private pension funds.